Progress of research on the relationship between efferocytosis and tumor - Yao, Xuexin; Zhang, Ling; Sun, Siyi; Fu, Aishuang; Ge, Yanlei (Frontiers in Oncology, 2024)
Tumors are genetic changes that develop in an organism as a result of many internal and external causes. They affect the biological behavior of cells, cause them to grow independently, and give rise to new, perpetually proliferating organisms.Recent research has supported the critical function of tumor-associated macrophages in the development, progression, and metastasis of tumors through efferocytosis. Yet, there is still much to learn about the mechanisms behind their contribution to tumor pathological processes. As a result, it's critical to actively investigate how cytosolic processes contribute to the growth of tumors and to create novel therapeutic approaches.